The mechanism of cytoplasmic streaming in characean algal cells: sliding of endoplasmic reticulum along actin filaments (The Rockefeller University Press, 1988)
Electron microscopy of directly frozen giant cells of characean algae shows a continuous, tridimensional network of anastomosing tubes and cisternae of rough endoplasmic reticulum which pervade the streaming region of their cytoplasm. Portions of this endoplasmic reticulum contact the parallel bundles of actin filaments at the interface with the stationary cortical cytoplasm. Mitochondria, glycosomes, and other small cytoplasmic organelles enmeshed in the endoplasmic reticulum network display Brownian motion while streaming. The binding and sliding of endoplasmic reticulum membranes along actin cables can also be directly visualized after the cytoplasm of these cells is dissociated in a buffer containing ATP. The shear forces produced at the interface with the dissociated actin cables move large aggregates of endoplasmic reticulum and other organelles. The combination of fast- freezing electron microscopy and video microscopy of living cells and dissociated cytoplasm demonstrates that the cytoplasmic streaming depends on endoplasmic reticulum membranes sliding along the stationary actin cables. Thus, the continuous network of endoplasmic reticulum provides a means of exerting motive forces on cytoplasm deep inside the cell distant from the cortical actin cables where the motive force is generated.